A simple but highly selective electrochemical sensor for dopamine - Doyle, Richard (Array, 2009)
Summary: A modified platinum electrode was fabricated by the electropolymerization of pyrrole using a sodium p-sulphonatocalix[6]arene as the supporting electrolyte. The modified electrode acts as a reasonably sensitive electrochemical sensor for dopamine giving a linear calibration curve in the range 0.075 – 1.00 mM dopamine. The sensor shows no ability to sense the common interferent ascorbic acid, therefore the concentration for dopamine can be directly sensed in a large excess of ascorbic acid with no need to make adjustments for the signal for ascorbic acid. Investigations are included to study the mode of sensing of the modified electrode